Bioconversion of restaurant waste into polyhydroxybutyrate (PHB) by recombinant E. coli through anaerobic digestion - Eshtaya, Majd Khalid; Abdul Rahman, Nor'aini; Hassan, Mohd Ali (Inderscience Enterprises, 2013)
The effect of temperature (30°C, 37°C, uncontrolled) and initial pH adjustment at pH 7 in the anaerobic digestion process was investigated to enhance the production of organic acids from restaurant waste. The highest organic acid level obtained was 39.6 g/L on the fifth day of fermentation conducted at 30°C and initial pH 7. The acids produced corresponded to 39.4% of the yield based on the initial concentration of substrate. The main organic acids produced were lactic and acetic acids. Using organic acids from fermented restaurant waste, recombinant Escherichia coli pnDTM2 gave PHB concentration, PHB content and PHB productivity of 9.2 g/L, 44% w/w and 0.54 g/L/h, respectively, in a pH stat fed-batch culture.